Manajemen Produksi Pembuatan Gamelan Di Besalen - Kartiman Kartiman (Riviera Publishing, 2025)
This article discusses the production management of gamelan manufacturing in besalen as a traditional industry that continues to uphold Javanese kinship values and culture. The study uses a descriptive qualitative method based on literature review and participatory observation to examine the organizational structure, task division, and technical processes involved in gamelan production. The findings reveal that the production process is closely tied to familial systems, where professionalism and a sense of responsibility are maintained. Roles such as panji, pemalu, pengalap, pengebang, and penyolok reflect a complex and harmonious social structure. In addition, flexible financial management, the use of traditional tools, and the preservation of local terminology in production processes highlight that the gamelan industry remains culturally rooted despite modern challenges.